THE EFFECT OF DIGITAL COMPETENCE AND RESONANT LEADERSHIP ON HIGH SCHOOL TEACHERS' PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN STATE SENIOR HIGH SCHOOL IN LHOKSUMAWE CITY - Muhammad Denni; Yusniar Lubis; Fajar Rezeki Ananda Lubis (Adisam Publisher, 2026)
Efforts to improve student achievement in a school environment cannot be separated from the role of teachers who must be more serious in implementing educational programs. Therefore, this study will test whether there is an influence of digital competence and resonant leadership on the performance of high school teachers with job satisfaction as an intervening variable and workload as a moderating variable at State Senior High Schools in Lhoksumawe City. Data collection was carried out quantitatively. This study involved teachers at high schools in Lhoksumawe City, Aceh. The results showed that digital competence and resonant leadership had a positive effect on teacher performance at Lhoksumawe City High Schools. In addition, digital competence and resonant leadership also had a positive effect on job satisfaction at Lhoksumawe City High Schools, and job satisfaction also had a positive effect on teacher performance.